Natural SEL1L variants rescue a model of NGLY1 deficiency and modify ERAD function and proteasome sensitivity. - Travis K Tu'ifua; Clement Y Chow (PLoS Genetics)
N-glycanase 1 (NGLY1) deficiency is an ultra-rare disease caused by autosomal recessive loss-of-function mutations in the NGLY1 gene. NGLY1 removes N-linked glycans from glycoproteins in the cytoplasm and is thought to help clear misfolded proteins from the endoplasmic reticulum (ER) through the ER associated degradation (ERAD) pathway. Despite this, the physiological significance of NGLY1 in ERAD is not understood. The best characterized substrate of NGLY1 is NRF1, a transcription factor that upregulates proteasome expression and the proteasome bounce-back response. We previously performed a genetic modifier screen using a Drosophila model of NGLY1 deficiency and identified potential modifiers that alter the lethality of the model. We identified two protein-coding variants in Hrd3/SEL1L: S780P and Δ806-809. Both variants are localized to the SEL1L cytoplasmic tail, an uncharacterized domain. SEL1L is a component of the ERAD complex that retrotranslocates misfolded proteins from the ER to the cytoplasm for degradation. We used CRISPR to generate fly lines carrying these SEL1L variants in a common genetic background and tested them with our model of NGLY1 deficiency. Validating our previous screen, the SEL1LS780P and SEL1LΔ806-809 variants increased the survival of the NGLY1 deficiency model, compared to the SEL1LS780 variant. To determine how these SEL1L variants were modifying lethality in NGLY1 deficiency, we interrogated the ERAD and NRF1 signaling pathways. We found that the SEL1LS780P and SEL1LΔ806-809 variants improve resistance to ER stress, with enhanced ERAD function as a likely contributing mechanism. This effect depends on NGLY1 activity, further implicating NGLY1 in general ERAD function. We also found that, in heterozygous NGLY1 null flies, these variants protect against some defects like increased lethality caused by proteasome inhibition. These results provide new insights into the role of SEL1L in the disease pathogenesis of NGLY1 deficiency. SEL1L is a strong candidate modifier gene in patients, where variability in presentation is common.